Allyl polar polyolefin elastomer as well as preparation method and application thereof

By introducing CH2=CH-(CH2)m-X polar monomer into the acrylic elastomer and carrying out copolymerization, the problem of the non-polar properties of the acrylic elastomer limiting its application is solved, and the improvement of material performance and compatibility is achieved.

CN119874981APending Publication Date: 2025-04-25合肥中科科乐新材料有限责任公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510125929.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The non-polar properties of acrylic-based elastomers limit their application between toughened polar plastics, compatibilized non-polar polyolefins and polar fillers, and the prior art is difficult to effectively introduce polar groups to improve material performance.

Method used

The propylene-based polar polyolefin elastomer with polar groups was obtained by copolymerizing the propylene monomer, CH2=CH-(CH2)n-CH3 monomer and CH2=CH-(CH2)m-X polar monomer in the presence of a specific hafnium catalyst or a titanium catalyst.

Benefits of technology

The effective introduction of polar groups in the material is achieved, the mechanical properties of the polymer, the molecular weight and compatibility of the polymer are improved, the compatibility with other polar olefin materials is enhanced, and the impact resistance, tensile strength and elongation of the break of the blended materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874981A_ABST
    Figure CN119874981A_ABST
Patent Text Reader

Abstract

The invention provides a propenyl polar polyolefin elastomer as well as a preparation method and application thereof, and belongs to the technical field of functional polymer polyolefin materials. Wherein the allyl polar polyolefin elastomer is a ternary random copolymer or an acidified product of the ternary random copolymer formed by copolymerizing a CH2 = CH2-CH3 monomer, a CH2 = CH-(CH2) n-CH3 monomer and a CH2 = CH-(CH2) m-X polar monomer; wherein the ternary random copolymer has a general formula structure as shown in a formula (1): # imgabs0 # formula (1), n is an integer of 1-8, m is an integer of 0-10, and y represents the degree of polymerization and is 50-20000; # imgabs 1 # represents an interval symbol between the monomers; x is selected from at least one of-F,-Cl,-Br,-I,-CN,-C (= O) O-CH3, # imgabs2 # or # imgabs3 #, R1, R2 and R3 are respectively and independently selected from any one of C1-C16 alkyl and C1-C16 alkyl substituted phenyl, and at least one of R1, R2 and R3 is selected from C1-C16 alkyl; the acidified product has a general formula structure as shown in a formula (2): # imgabs4 #, wherein M is selected from at least one of-F,-Cl,-Br,-I,-CN,-OH,-C (= O) O-CH3 or-COOH.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional polymer polyolefin materials, and in particular relates to a propylene-based polar polyolefin elastomer and a preparation method and application thereof. Background Art

[0002] Propylene-based elastomer is a low-crystalline polymer with amorphous regions as the main raw material, which is obtained by solution polymerization with propylene as the main raw material and a small amount of α-olefin monomer added. The introduced α-olefin weakens the crystallization between carbon and carbon, forming elastic amorphous regions. Therefore, propylene-based polyolefin elastomer is composed of a crystalline phase and an amorphous rubber phase, which gives the material thermoplasticity and high elasticity, as well as high transparency and low-temperature toughness. It also has good compatibility with olefin polymers, especially polypropylene, and is therefore widely used to improve the optical properties, sealing, hot viscosity, elasticity, toughness and softness of polyolefins.

[0003] However, due to the non-polar properties of propylene-based elastomers, their application in certain fields is limited, such as toughening polar plastics, compatibility of non-polar polyolefins and polar filler additives. Introducing a small amount of polar groups into non-polar polyolefins can significantly improve their surface properties, compatibility, hydrophilicity, dyeability, etc. Therefore, ways to introduce polar groups into non-polar polyolefins have been sought for a long time. Post-polymerization functionalization is the most commonly used method to introduce polar functional groups into homopolymers. However, since the carbon-hydrogen bonds of the polyolefin main chain are too inert, post-modification of alkanes is difficult, and high-temperature and high-shear blending methods are prone to side reactions such as cross-linking and chain scission. The direct copolymerization of olefins and polar monomers based on the free radical mechanism requires high temperature and high pressure (up to 375°C and 300MPa, respectively), with high costs and risks. In addition, due to the lack of effective means to regulate the copolymerization process, the materials produced often have a wide molecular weight distribution and poor performance. Compared with the free radical mechanism, single-active-site transition metal catalysts are used for coordination insertion polymerization, which can effectively regulate the polymer structure, but they have more stringent requirements on catalytic activity, substrate compatibility, polymerization conditions, etc. Therefore, it is necessary to prepare propylene-based polar polyolefin elastomers through a relatively simple and easy-to-control method. Summary of the invention

[0004] In view of the above technical problems, the present disclosure provides a propylene-based polar polyolefin elastomer and a preparation method and application thereof, in order to at least partially solve the above technical problems. In this regard, the technical solution provided by the present disclosure is as follows.

[0005] As a first aspect of the present disclosure, a propylene-based polar polyolefin elastomer is provided. The propylene-based polar polyolefin elastomer is a CH2=CH2-CH3 monomer, CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2)m -X polar monomer copolymerization formed by terpolymer or its acidification product;

[0006] The ternary random copolymer has a general structure as shown in formula (1): Formula (1), n ​​is an integer of 1-8, m is an integer of 0-10, and y represents the degree of polymerization, which is 50-20000; represents the spacer symbol between monomers; X is selected from -F, -Cl, -Br, -I, -CN, -C(=O)O-CH3, or At least one of, R1, R2, R3 are each independently selected from C1-C 16 Alkyl, C1-C 16 Any of the alkyl-substituted phenyl groups, at least one of R1, R2, and R3 is selected from C1-C 16 alkyl;

[0007] The acidified product has a general structure as shown in formula (2): Formula (2), wherein M is selected from at least one of -F, -Cl, -Br, -I, -CN, -OH, -C(=O)O-CH3 or -COOH.

[0008] As a second aspect of the present disclosure, a method for preparing a propylene-based polar polyolefin elastomer is provided, comprising: converting CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m -X polar monomer, polymerization solvent, and scavenger are added into the reactor, CH2=CH2-CH3 monomer gas is introduced and the temperature is raised to the polymerization reaction temperature, and then the main catalyst and the co-catalyst are introduced to carry out polymerization reaction to obtain a ternary random copolymer; and optionally, the ternary random copolymer is acidified to obtain a propylene-based polar polyolefin elastomer;

[0009] Wherein, n is an integer of 1-8, m is an integer of 0-10, and X is selected from -F, -Cl, -Br, -I, -CN, -C(=O)O-CH3, or At least one of, R1, R2, R3 are each independently selected from C1-C 16 Alkyl, C1-C 16 Any of the alkyl-substituted phenyl groups, at least one of R1, R2, and R3 is selected from C1-C 16 alkyl;

[0010] The main catalyst has a structure as shown in formula (3) or formula (4): Formula (3) or Formula (4), wherein R4 is selected from phenyl, C1-C4 alkyl substituted phenyl, 、N-C1-C 16 Alkyl, C1-C 16 At least one of the alkyl groups; R5 and R6 are each independently selected from Cl, C1-C 16 Any one of alkyl, phenyl, and C1-C4 alkyl-substituted phenyl; R7 is selected from , , Any one of .

[0011] As a third aspect of the present disclosure, there is provided a use of a propylene-based polar polyolefin elastomer as a compatibilizer.

[0012] Based on the above technical solution, the propylene-based polar polyolefin elastomer and its preparation method and application provided by the present disclosure have at least one of the following beneficial effects:

[0013] (1) In the embodiments of the present disclosure, propylene and CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m -X polar monomers for copolymerization, using CH2=CH-(CH2) n -CH3 monomer improves the mechanical and elastic properties of the final polymer, utilizing CH2=CH-(CH2) m -X polar monomers are used to introduce polar groups into the final polymer, thereby obtaining propylene-based polar polyolefin elastomers with more functionality, higher polymer molecular weight and excellent mechanical properties.

[0014] (2) In the embodiments of the present disclosure, propylene monomer, CH2=CH-(CH2) n -CH3 monomer, CH2=CH-(CH2) m -X polar monomer, polymerization solvent and scavenger are added into the reactor, and a catalytic polymerization reaction occurs in the presence of a specific hafnium catalyst or titanium catalyst and a co-catalyst, and the obtained ternary random copolymer or its acidified product has a higher polymer molecular weight and excellent mechanical properties.

[0015] (3) In the embodiments of the present disclosure, by introducing CH2=CH-(CH2) into the final polymer m -X polar monomers help to improve the compatibility of the final polymer with other polar olefin materials and improve the mechanical properties of the blended materials, such as impact resistance, tensile strength, elongation at break, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The stress-strain curves of the blended materials in Application Example 1 and Comparative Example 1;

[0017] Figure 2 The stress-strain curves of the blended materials in Application Example 2 and Comparative Example 2;

[0018] Figure 3 This is a graph showing the impact strength of the blended materials in Application Example 1-2 and Comparative Example 1-2;

[0019] Figure 4 This is a scanning electron microscope (SEM) image of the blended material in Comparative Example 1;

[0020] Figure 5 This is a scanning electron microscope (SEM) image of the blended material in Application Example 1;

[0021] Figure 6 The stress-strain curves of the blended materials in Application Example 3 and Comparative Example 3;

[0022] Figure 7 This is a scanning electron microscope (SEM) image of the blended material in Comparative Example 3;

[0023] Figure 8 This is a scanning electron microscope (SEM) image of the blended material in Application Example 3. DETAILED DESCRIPTION

[0024] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present disclosure. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present disclosure. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concepts of the present disclosure.

[0025] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0026] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).

[0027] In view of the non-polar characteristics of propylene-based elastomers, their applications in toughening polar plastics, compatibilizing non-polar polyolefins and polar fillers are limited. The present disclosure proposes to combine propylene monomer, α-olefin (CH2=CH-(CH2) n -CH3 monomer) and CH2=CH-(CH2) m -X polar monomers are copolymerized in the presence of specific hafnium catalysts or titanium catalysts under relatively mild reaction conditions to obtain propylene-based polar polyolefin elastomers with polar monomers. The propylene-based polar polyolefin elastomers contain polar groups, which can be used to compatibilize blends of non-polar polyolefins and polar fillers, and the obtained blends have excellent mechanical properties.

[0028] Specifically, as a first aspect of the present disclosure, a propylene-based polar polyolefin elastomer is provided, wherein the propylene-based polar polyolefin elastomer is a CH2=CH2-CH3 monomer, CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m -X polar monomer copolymerization formed by terpolymer random copolymer or its acidification product.

[0029] The ternary random copolymer has a general structure as shown in formula (1): Formula (1), n ​​is an integer of 1-8, m is an integer of 0-10, and y represents the degree of polymerization, which is 50-20000; represents the spacer symbol between monomers; X is selected from -F, -Cl, -Br, -I, -CN, -C(=O)O-CH3, or At least one of, R1, R2, R3 are each independently selected from C1-C 16 Alkyl, C1-C 16 Any of the alkyl-substituted phenyl groups, at least one of R1, R2, and R3 is selected from C1-C16 alkyl.

[0030] The acidified product has a general structure as shown in formula (2): Formula (2), wherein M is selected from at least one of -F, -Cl, -Br, -I, -CN, -OH, -C(=O)O-CH3 or -COOH.

[0031] In the embodiments of the present disclosure, propylene is reacted with CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m -X polar monomers for copolymerization, using CH2=CH-(CH2) n -CH3 monomer improves the mechanical and elastic properties of the final polymer, utilizing CH2=CH-(CH2) m -X polar monomers are used to introduce polar groups into the final polymer, thereby increasing the compatibility of the polymer.

[0032] According to the embodiments of the present disclosure, the term "random copolymer" refers to the above-mentioned propylene monomer (CH2=CH2-CH3 monomer), CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m - A terpolymer formed by random copolymerization of a polar monomer X, or a copolymer formed by acidification with hydrochloric acid.

[0033] According to the embodiments of the present disclosure, formula (1) only represents that the random copolymer of the present disclosure is composed of CH2=CH2-CH3 monomers, CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m -X polar monomers (separated by the symbol " / " in (1)) are copolymerized or have three repeating units, but it does not mean that the random copolymer disclosed in the present invention is polymerized by the three monomers in an equal molar ratio, such as a molar ratio of 1:1:1. In fact, due to the different copolymerization activities of the early transition metal catalyst (main catalyst, i.e., hafnium catalyst or titanium catalyst) used in the preparation process when catalyzing the three different monomers used, the molar content of each monomer in the obtained random copolymer can vary greatly.

[0034] According to the embodiment of the present disclosure, C1-C 16 Alkyl refers to a straight chain, branched or cyclic alkyl group having 1 to 16 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, neopentyl, n-hexyl, etc. or their isomeric forms.

[0035] According to embodiments of the present disclosure, the symbol "-" in the group represented by X means that the mentioned group is connected to the rest of the molecule at the atom where the symbol is located. For example, the group "-C(=O)O-CH3alkyl" means that the alkyl ester group is connected to the rest of the corresponding molecule through the carbonyl carbon (C) atom.

[0036] According to an embodiment of the present disclosure, m is an integer of 4-10, and X is selected from -C(=O)O-CH3, or At least one of -OH, -C(=O)O-CH3 or -COOH; M is selected from at least one of -OH, -C(=O)O-CH3 or -COOH. The propylene-based polar polyolefin elastomer obtained by the introduction of -OH, -C(=O)O-CH3 or -COOH can increase the surface properties, compatibility, dyeability, etc. of non-polar polymers (such as polypropylene) as a compatibilizer.

[0037] According to an embodiment of the present disclosure, in the propylene-based polar polyolefin elastomer, CH2=CH-(CH2) m -The insertion ratio of the X polar monomer is 1.5-3.0%, indicating that the disclosed propylene-based polar polyolefin elastomer has excellent compatibility. The number average molecular weight of the propylene-based polar polyolefin elastomer is 5,000-200,000, the polymer dispersibility index is 1.4-2.5, and the glass transition temperature is -8°C~-24°C, so that the propylene-based polar polyolefin elastomer polymer performs well in the compatibilization of polypropylene and talcum powder composites, and polypropylene and pine wood powder composites. Among them, in the composite material of polypropylene and talcum powder, adding 5% mass fraction of propylene-based polar elastomer, in the blended material with 20% talcum powder, the elongation at break is increased by 297%, and the impact strength is increased by 164%; in the blended material with 40% talcum powder, the elongation at break is increased by 159%, and the impact strength is increased by 154%. Among them, in the composite material of polypropylene and pine wood powder, adding 10% mass fraction of propylene-based polar elastomer, its tensile strength is increased by 30%, and the elongation at break is increased by 138%.

[0038] As a second aspect of the present disclosure, a method for preparing a propylene-based polar polyolefin elastomer is provided, comprising: converting CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m -X polar monomer, polymerization solvent, and scavenger are added into the reactor, CH2=CH2-CH3 monomer gas is introduced and the temperature is raised to the polymerization reaction temperature, and then the main catalyst and the co-catalyst are introduced to carry out polymerization reaction to obtain a ternary random copolymer; and optionally, the ternary random copolymer is subjected to acidification treatment to obtain a propylene-based polar polyolefin elastomer; wherein n is an integer of 1-8, m is an integer of 0-10, and X is selected from -F, -Cl, -Br, -I, -CN, -C(=O)O-CH3, or At least one of, R1, R2, R3 are each independently selected from C1-C 16 Alkyl, C1-C 16 Any of the alkyl-substituted phenyl groups, at least one of R1, R2, and R3 is selected from C1-C 16 alkyl.

[0039] The main catalyst is a titanium (Ti) catalyst or a hafnium (Hf) catalyst having a structure as shown in formula (3) or formula (4): Formula (3) or Formula (4), wherein R4 is selected from phenyl, C1-C4 alkyl substituted phenyl, 、N-C1-C 16 Alkyl, C1-C 16 At least one of the alkyl groups; R5 and R6 are each independently selected from Cl, C1-C 16 Any one of alkyl, phenyl, and C1-C4 alkyl-substituted phenyl; R7 is selected from , , Any one of .

[0040] In the embodiments of the present disclosure, propylene monomer, CH2=CH-(CH2) n -CH3 monomer, CH2=CH-(CH2) m -X polar monomer, polymerization solvent and scavenger are added into the reactor, and a catalytic polymerization reaction occurs in the presence of a specific hafnium catalyst or titanium catalyst and a co-catalyst. The obtained ternary random copolymer or its acidified product has a higher polymer molecular weight and excellent mechanical properties.

[0041] According to an embodiment of the present disclosure, the co-catalyst is selected from , , Any one of .

[0042] According to an embodiment of the present disclosure, the cleaning agent is selected from C1-C 16 Alkyl aluminoxane, C1-C 16 Alkyl aluminum, C1-C4 alkyl substituted aluminum chloride, C1-C4 alkyl substituted phenyl aluminum, C6-C 18 Any one of the aryl aluminums. Specifically, C1-C 16 The alkylaluminoxane is selected from any one of methylaluminoxane, ethylaluminoxane, butylaluminoxane and hexylaluminoxane. 16The alkylaluminum is selected from any one of trimethylaluminum, triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum, triisopropylaluminum, triisobutylaluminum, tripentylaluminum, trihexylaluminum, tricyclohexylaluminum, and trioctylaluminum. The C1-C4 alkyl-substituted aluminum chloride is selected from any one of diethylaluminum chloride. The C1-C4 alkyl-substituted phenylaluminum is selected from any one of triphenylaluminum and tri-p-tolylaluminum. 18 The aryl aluminum is selected from any one of tribenzyl aluminum, ethyl dibenzyl aluminum, ethyl di-p-tolyl aluminum and diethylbenzyl aluminum. In the embodiments of the present disclosure, impurities such as moisture and oxygen in the polymerization reaction are removed by a scavenger to ensure the catalytic activity of the catalyst and increase the yield of the polymer.

[0043] According to an embodiment of the present disclosure, the polymerization solvent is selected from at least one of toluene, xylene, chlorobenzene, n-hexane, n-heptane, and methylcyclohexane. Further, the present disclosure can carry out the polymerization reaction in the presence of an additional organic solvent, that is, the polymerization reaction is carried out in a solution, and thus can also be referred to as a solution polymerization reaction.

[0044] According to an embodiment of the present disclosure, the polymerization temperature is 0-180°C, for example, 10°C, 20°C, 30°C, 50°C, 100°C, 120°C, 150°C, 180°C, etc., within which the main catalyst and the co-catalyst can stably exist and exert catalytic performance. The propylene pressure is 1-10atm, preferably 1-8atm, more preferably 1-4atm. The polymerization time is 0.1h-12h, preferably 0.1-2h, for example, 0.1h, 0.5h, 2h, 4h, 6h, 8h, 10h, 12h.

[0045] According to an embodiment of the present disclosure, CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m - The concentration of the polar monomers X is independently 0.01-10 mol / L, wherein CH2=CH-(CH2) n The concentration of -CH3 monomer is preferably 0.1-4 mol / L, CH2=CH-(CH2) m The concentration of the -X polar monomer is preferably 0.1-2 mol / L.

[0046] According to an embodiment of the present disclosure, during the solution polymerization process, the sweeping agent reacts with CH2=CH-(CH2) m -X polar monomer molar ratio is 1.05-1.2:1. The main catalyst dosage can be 1.0-200 μmol, and the molar ratio of the co-catalyst to the main catalyst is (1-20):1, CH2=CH-(CH2) n-The molar ratio of CH3 monomer to main catalyst is (2000-100000):1, CH2=CH-(CH2) m -The ratio of X polar monomer to main catalyst is (2000-50000): 1, the co-catalyst used is CH2=CH-(CH2) m -X polar monomer ratio is (1.05-3): 1. For example, when the concentration of the main catalyst used is 2.5 μmol, CH2=CH-(CH2) n -CH3 monomer concentration is 40mmol, CH2=CH-(CH2) m The concentration of -X polar monomer is 8 mmol.

[0047] According to the embodiments of the present disclosure, the present disclosure is for realizing CH2=CH2-CH3 monomers, CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m The reactor for the copolymerization of -X polar monomers is not particularly limited, generally as long as the desired copolymerization can be achieved. Preferably, the copolymerization of the present disclosure can be carried out in a reactor. More preferably, the reactor is in an inert atmosphere, such as a nitrogen atmosphere. The temperature of the reactor can be achieved by a water bath heating or an oil bath heating system.

[0048] More specifically, the preparation method of the propylene-based polar polyolefin elastomer comprises: CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m -X polar monomer, n-heptane (polymerization solvent) and scavenger are added to the polymerization reactor, and CH2=CH2-CH3 monomer gas is introduced. After heating to the specified temperature, the required main catalyst (such as titanium catalyst or hafnium catalyst) and co-catalyst are injected, and the pressure of propylene is adjusted to the specified pressure. After polymerization for a certain period of time, a ternary random copolymer is obtained. Subsequently, a large amount of hydrochloric acid acetone solution is added to quench, and a white polymer is obtained by filtration, which is further extracted by a Soxhlet extractor to remove the residual CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m -X polar monomer, thereby obtaining the acidified product of the terpolymer.

[0049] As a third aspect of the present disclosure, there is provided a use of a propylene-based polar polyolefin elastomer as a compatibilizer.

[0050] In the embodiments of the present disclosure, the CH2=CH-(CH2) introduced into the final polymer is used. m-X polar monomers help to improve the compatibility of the final polymer with other polar olefin materials and improve the mechanical properties of the blended materials, such as impact resistance, tensile strength, elongation at break, etc.

[0051] According to an embodiment of the present disclosure, a propylene-based polar polyolefin elastomer is used as a compatibilizer to compatibilize talcum powder or pine wood powder. Specifically, the method of compatibilizing talcum powder or pine wood powder with a compatibilizer comprises: blending a propylene-based polar polyolefin elastomer, polypropylene and a compatibilization object, and obtaining a blended material after extrusion, wherein the compatibilization object is talcum powder or pine wood powder. Wherein, in parts by weight, the propylene-based polar polyolefin elastomer is 2-20 parts, the polypropylene is 40-72 parts, and the compatibilization object is 20-40 parts, totaling 100 parts.

[0052] In the embodiments of the present disclosure, a propylene-based polar polyolefin elastomer is used as a compatibilizer and blended with polypropylene and a compatibilization object. The polar groups contained in the propylene-based polar polyolefin elastomer can improve the compatibility of polypropylene and the compatibilization object (such as talcum powder or pine wood powder), thereby making the talcum powder or pine wood powder evenly dispersed in the polypropylene, thereby improving the mechanical properties of the blended material.

[0053] According to an embodiment of the present disclosure, the method of compatibilizing talcum powder or pine wood powder with a compatibilizer further includes: adding an antioxidant to blend with the propylene-based polar polyolefin elastomer, polypropylene and the compatibilization object; wherein the antioxidant is 0.2-0.4 parts by weight.

[0054] In an embodiment of the present disclosure, the service life of the blended material is extended by adding an antioxidant.

[0055] According to an embodiment of the present disclosure, the antioxidant is selected from one or more of 2,6-di-tert-butyl-p-cresol, antioxidant 1010 and antioxidant 168 .

[0056] In order to further illustrate the technical solution of the present disclosure, the propylene-based polar polyolefin elastomer provided by the present disclosure and its preparation method and application are described in detail below in conjunction with the examples. However, it should be understood that these examples are only used for the purpose of illustrating to help understand the concept of the present disclosure, rather than limiting the protection scope of the present disclosure, and the protection scope of the present disclosure is not limited to the following examples.

[0057] The sources of the raw materials in the following examples of the present disclosure are not particularly limited, and the raw materials can be prepared by methods well known to those skilled in the art or purchased from the market.

[0058] The data given in the examples include the specific process and parameters of the monomer copolymerization. The polymerization process is carried out in an inert atmosphere or environment without water or oxygen. All sensitive substances are stored in a glove box or refrigerator at -30°C. All solvents are strictly dried and dehydrated. Unless otherwise specified, all other raw materials are used directly after purchase.

[0059] Example 1

[0060] Propylene, 1-octene (Oct) and (CH2=CH-(CH2)9-OSiMe3 polar monomer (abbreviated as: m-OSiMe3) are used as raw materials to prepare propylene-based polar polyolefin elastomer. The specific preparation process is as follows.

[0061] In a glove box, under a nitrogen atmosphere, n-heptane solvent was added to a 350 mL reactor, wherein the total volume of the reactants was 40 mL. For the random copolymer P / Oct(0.5) / m-OSiMe3(0.2) prepared in Example 1, the molar number of 1-octene (Oct) monomer was 20 mmol, and the molar number of m-OSiMe3 polar monomer was 8 mmol, and a scavenger (triisobutylaluminum) equivalent to 1.1 equivalents of m-OSiMe3 polar monomer was added to the reactor. Then, the propylene (CH2=CH2-CH3 monomer) gas source pipeline was connected to pass propylene (P monomer for short) gas into the reactor, and the reactor was heated to 30°C by water bath heating under magnetic stirring, and 2 μmol of the main catalyst dissolved in 1 mL of toluene and 1.5 equivalents of the co-catalyst [Ph3C][B(C6F5)4] were added to the reactor, and the propylene pressure was adjusted to 8 atm and the reaction was carried out under magnetic stirring for 2 h. After the reaction is completed, the excess gas is released, and then the reactor is opened. 50 mL of acetone hydrochloride is added to the obtained reaction solution for quenching. Finally, it is filtered under reduced pressure, and the obtained solid product is dried in a vacuum drying oven at 50°C for 24 hours to obtain a white solid, which is the desired propylene-based polar polyolefin elastomer P / Oct(0.5) / m-OSiMe3(0.2), wherein the molar concentration of each monomer is indicated in brackets after the corresponding comonomer. The main catalyst used in Example 1 is a hafnium catalyst, and the specific structure is shown in the following formula (4-1). Calculate the product yield (i.e., the mass of the copolymer obtained during the polymerization time (g)) and the reaction activity (in g·mol -1 ·h -1 , that is, the mass of copolymer produced by polymerization per mole of catalyst per hour). The specific test results are shown in Table 1.

[0062] Formula (4-1) is a hafnium catalyst.

[0063] Example 2

[0064] Example 2: A propylene-based polar polyolefin elastomer is prepared by the same method as in Example 1, with the only difference being that when the total reactant volume is 40 mL, the molar number of 1-octene (Oct) monomer is 40 mmol, and the molar number of m-OSiMe3 polar monomer is 8 mmol, and the obtained propylene-based polar polyolefin elastomer is P / Oct(1) / m-OSiMe3(0.2).

[0065] Example 3

[0066] Example 3: A propylene-based polar polyolefin elastomer is prepared by the same method as in Example 1, with the only difference being that, when the total reactant volume is 40 mL, the molar number of 1-octene (Oct) monomer is 20 mmol, and the molar number of CH2=CH-(CH2)8-COOSiMe3 polar monomer (abbreviated as m-COOSiMe3) is 8 mmol, and the obtained propylene-based polar polyolefin elastomer is P / Oct(0.5) / m-COOSiMe3(0.2).

[0067] Example 4

[0068] Example 4 The same method as in Example 1 was used to prepare a propylene-based polar polyolefin elastomer, with the only difference being that when the total reactant volume was 40 mL, the molar number of 1-octene (Oct) monomer was 40 mmol, and the molar number of CH2=CH-(CH2)8-COOSiMe3 polar monomer (abbreviated as m-COOSiMe3) was 8 mmol, and the obtained propylene-based polar polyolefin elastomer was P / Oct(1) / m-COOSiMe3(0.2).

[0069] Example 5

[0070] Example 5 The same method as in Example 1 was used to prepare a propylene-based polar polyolefin elastomer, with the only difference being that when the total reactant volume was 40 mL, a titanium catalyst was used as the main catalyst, the molar number of 1-octene (Oct) monomer was 20 mmol, and the molar number of (CH2=CH-(CH2)9-OSiMe3 polar monomer (abbreviated as: m-OSiMe3) was 8 mmol, and the obtained propylene-based polar polyolefin elastomer was P / Oct(0.5) / m-OSiMe3(0.2). The structure of the titanium catalyst is shown in Formula (3-1).

[0071] Formula (3-1) titanium catalyst.

[0072] Example 6

[0073] Example 6 The same method as in Example 5 was used to prepare a propylene-based polar polyolefin elastomer, with the only difference being that when the total reactant volume was 40 mL, a titanium catalyst was used as the main catalyst, the molar number of 1-octene (Oct) monomer was 40 mmol, and the molar number of (CH2=CH-(CH2)9-OSiMe3 polar monomer (abbreviated as: m-OSiMe3) was 8 mmol, and the obtained propylene-based polar polyolefin elastomer was P / Oct(1) / m-OSiMe3(0.2).

[0074] The mechanism routes for preparing propylene-based polar polyolefin elastomers in the above-mentioned Examples 1 to 6 are as follows:

[0075]

[0076] Among them, the formula represents propylene monomer (P), formula represents 1-octene monomer (Oct), Represents a polar monomer, X represents -CH2OSiMe3, -COOSiMe3, M represents -CH2OH or -COOH; y is the degree of polymerization which can be in the range of 50~20000.

[0077] The monomer insertion ratio was 1 H NMR or 13 C NMR spectra in deuterated tetrachloroethane (C2D2Cl4) at 120 o C, indicating the percentage of 1-octene monomer (Oct) or polar monomer in the obtained copolymer polymer chain, and the higher the insertion ratio, the higher the proportion of the polar monomer or 1-octene monomer in the copolymer polymer chain.

[0078] The obtained propylene-based polar polyolefin elastomer was measured by high temperature gel permeation chromatography GPC (trichlorobenzene as solvent, test temperature of 150°C). n ) and polymer dispersibility index (PDI); differential scanning calorimetry (DSC, scanning temperature range -50-150 o C, the heating rate is 10 o C / min) to measure the melting point T of the product m and glass transition temperature T g The results are shown in Table 1 below.

[0079] Table 1

[0080]

[0081] Note: : =40 mL, T=30°C, propylene pressure=4 atm, polymerization time=2h; g·mol -1 ·h -1 ; Insertion ratio; and polydispersity index PDI measured by GPC; Measured by DSC.

[0082] As shown in Table 1, the propylene-based polar polyolefin elastomer prepared by the method provided by the present disclosure has a relatively high molecular weight, and the number average molecular weight is above 180,000. At the same time, the dispersion index (PDI) of the propylene-based polar polyolefin elastomer obtained by the present disclosure is relatively narrow, mainly concentrated in the range of 1.4-2.2. In addition, the insertion ratio of the polar monomer in the obtained polymer is as high as 2.86%.

[0083] Application Example 1

[0084] The propylene-based polar elastomer (P / Oct(0.5) / m-OSiMe3(0.2)) prepared in Example 1 was blended with Z30S polypropylene and talcum powder purchased from Sinopec to prepare a blend material, and its mechanical properties were investigated.

[0085] Specifically, P / Oct(0.5) / m-OSiMe3(0.2), Z30S, and talc were weighed in a weight ratio of 8:72:20, and 0.2% of the antioxidant 2,6-di-tert-butyl-p-cresol was added for mixing. The mixed materials were transported to a twin-screw extruder for blending and extrusion, wherein the extruder operating temperature was 180°C and the mixing time was 6 minutes, thereby obtaining a blended material of P / Oct(0.5) / m-OSiMe3(0.2) / Z30S / talc 8 / 72 / 20.

[0086] Application Example 2

[0087] The blended material was prepared by the same method as in Application Example 1, with the only difference being that the weight ratio of P / Oct(0.5) / m-OSiMe3(0.2), Z30S polypropylene and talcum powder was 8:52:40, yielding P / Oct(0.5) / m-OSiMe3(0.2) / Z30S / talcum powder 8 / 52 / 40.

[0088] Comparative Example 1

[0089] The blend material was prepared by the same method as in Application Example 1, with the only difference being that the propylene-based polar polyolefin elastomer P / Oct(0.5) / m-OSiMe3(0.2) was not added, but the weight ratio of Z30S type polypropylene and talc was 80:20, thereby obtaining a blend material of Z30S / talc 80 / 20.

[0090] Comparative Example 2

[0091] The blend material was prepared by the same method as in Application Example 1, with the only difference being that the propylene-based polar polyolefin elastomer P / Oct(0.5) / m-OSiMe3(0.2) was not added, but the weight ratio of Z30S type polypropylene and talc was 60:40, thereby obtaining a Z30S / talc 60 / 40 blend material.

[0092] Application Example 3

[0093] The blend material was prepared by the same method as in Application Example 1, with the only difference being that propylene-based polar polyolefin elastomer P / Oct(0.5) / m-OSiMe3(0.2) was added to blend with Z30S type polypropylene and pine wood powder, and the weight ratio of the three was 10:60:30, thus obtaining a blend material of P / Oct(0.5) / m-OSiMe3(0.2) / Z30S / pine wood powder 10 / 60 / 30.

[0094] Comparative Example 3

[0095] The blend material was prepared by the same method as in Application Example 1, with the only difference being that the propylene-based polar polyolefin elastomer P / Oct(0.5) / m-OSiMe3(0.2) was not added, but the weight ratio of Z30S type polypropylene and pine wood powder was 70:30, thereby obtaining a blend material of Z30S / pine wood powder 70 / 30.

[0096] The blend materials prepared in Application Example 1, Application Example 2, Comparative Example 1 and Comparative Example 2 were subjected to stress-strain curve, cantilever beam impact strength test and brittle fracture scanning electron microscope (SEM) characterization, and the test results are as follows: Figure 1-Figure 5 shown.

[0097] Figure 1 The stress-strain curves of the blended materials in Application Example 1 and Comparative Example 1 are as follows: Figure 2 The stress-strain curves of the blended materials in Application Example 2 and Comparative Example 2 are as follows: Figure 3 This is a graph of the impact strength of the blended materials in Application Example 1-2 and Comparative Example 1-2.

[0098] like Figure 1-Figure 3As shown in the figure, the performance of the blend of P / Oct(0.5) / m-OSiMe3(0.2), Z30S and talc is basically the same as that of the blend of Z30S and talc, but the elongation at break of the blend is significantly improved after adding P / Oct(0.5) / m-OSiMe3(0.2), where the elongation at break is increased by 297% in the blend with 20% talc and by 159% in the blend with 40% talc. Furthermore, the impact strength of the blend is also significantly improved after adding P / Oct(0.5) / m-OSiMe3(0.2), where the elongation at break is increased by 164% in the blend with 20% talc and by 154% in the blend with 40% talc.

[0099] Further, the morphology of the blended materials in Example 1 and Comparative Example 1 was analyzed, and the specific test results are as follows: Figure 4 and Figure 5 shown.

[0100] Figure 4 This is a scanning electron microscope (SEM) image of the blended material in Comparative Example 1. Figure 5 This is a scanning electron microscope (SEM) image of the blended material in Application Example 1.

[0101] like Figure 4 As shown, there is obvious phase separation in the blend of Z30S / talcum powder, while each phase is evenly dispersed in the blend of P / Oct(0.5) / m-OSiMe3(0.2) / Z30S / talcum powder, and there is no obvious phase separation. This shows that the propylene-based polar polyolefin elastomer prepared in the present disclosure has good compatibility, which can effectively promote the uniform mixing of non-polar polypropylene and polar filler additives (such as talcum powder), thereby improving the performance of the blended material.

[0102] Furthermore, the blend materials prepared in Application Example 3 and Comparative Example 3 were subjected to stress-strain curve, cantilever beam impact strength test and brittle fracture scanning electron microscope (SEM) characterization, and the test results are as follows: Figure 6-Figure 8 shown.

[0103] Figure 6 The stress-strain curves of the blended materials in Application Example 3 and Comparative Example 3 are as follows: Figure 7 This is a scanning electron microscope (SEM) image of the blended material in Comparative Example 3. Figure 8 This is a scanning electron microscope (SEM) image of the blended material in Application Example 3.

[0104] like Figure 6As shown, the performance of the blend of P / Oct(0.5) / m-OSiMe3(0.2) / Z30S / pine wood powder is 30% higher in tensile strength and 138% higher in elongation at break than that of the blend of Z30S / pine wood powder. Furthermore, it can be seen from the SEM image that the phase separation is serious in the blend of Z30S / pine wood powder (70 / 30), while in the blend of P / Oct(0.5) / m-OSiMe3(0.2) / Z30S / pine wood powder 10 / 60 / 30, it can be seen that the structure is uniform, the pine wood powder is evenly dispersed, and there is no obvious phase separation. This shows that the propylene-based polar polyolefin elastomer prepared in the present disclosure has good compatibility, can effectively promote the uniform mixing of non-polar polypropylene plastics and polar filler additives (such as pine wood powder), and improve the performance of the composite material.

[0105] In summary, the polar groups in the propylene-based polar elastomer disclosed in the present invention have good compatibility with polar fillers (such as talcum powder and pine wood powder), and the main chain in the propylene-based polar elastomer has good compatibility with non-polar polypropylene. Therefore, the propylene-based polar elastomer can effectively enhance the compatibility between polypropylene and polar fillers.

[0106] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.

Claims

1. A propylene-based polar polyolefin elastomer, characterized in that: The propylene-based polar polyolefin elastomer is a CH2=CH2-CH3 monomer, CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m -X polar monomer copolymerization formed by terpolymer or its acidification product, The ternary random copolymer has a general structure as shown in formula (1): Formula (1), n ​​is an integer of 1-8, m is an integer of 0-10, and y represents the degree of polymerization, which is 50-20000; represents the spacer symbol between monomers; X is selected from -F, -Cl, -Br, -I, -CN, -C(=O)O-CH3, or At least one of, R1, R2, R3 are each independently selected from C1-C 16 Alkyl, C1-C 16 Any of the alkyl-substituted phenyl groups, at least one of R1, R2, and R3 is selected from C1-C 16 alkyl; Wherein, the acidified product has a general structure as shown in formula (2): Formula (2), wherein M is selected from at least one of -F, -Cl, -Br, -I, -CN, -OH, -C(=O)O-CH3 or -COOH.

2. The propylene-based polar polyolefin elastomer according to claim 1, characterized in that: m is an integer of 4-10, X is selected from -C(=O)O-CH3, or At least one of the following; M is selected from at least one of -OH, -C(=O)O-CH3 or -COOH.

3. The propylene-based polar polyolefin elastomer according to claim 1, characterized in that: In the propylene-based polar polyolefin elastomer, the CH2=CH-(CH2) m -The insertion ratio of X-polar monomers is 1.5-3.0%; The number average molecular weight of the propylene-based polar polyolefin elastomer is 5,000-200,000, the polymer dispersibility index is 1.4-2.5, and the glass transition temperature is -8°C to -24°C.

4. A method for preparing a propylene-based polar polyolefin elastomer, characterized in that: The preparation method comprises: CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m -X polar monomer, polymerization solvent, and scavenger are added into the reactor, CH2=CH2-CH3 monomer gas is introduced and the temperature is raised to the polymerization reaction temperature, and then the main catalyst and the co-catalyst are introduced to carry out polymerization reaction to obtain a ternary random copolymer; and Optionally, the terpolymer is subjected to acidification treatment to obtain the propylene-based polar polyolefin elastomer as described in any one of claims 1 to 3; Wherein, n is an integer of 1-8, m is an integer of 0-10, and X is selected from -F, -Cl, -Br, -I, -CN, -C(=O)O-CH3, or At least one of, R1, R2, R3 are each independently selected from C1-C 16 Alkyl, C1-C 16 Any of the alkyl-substituted phenyl groups, at least one of R1, R2, and R3 is selected from C1-C 16 alkyl; The main catalyst has a structure as shown in formula (3) or formula (4): Formula (3) or Formula (4), wherein R4 is selected from phenyl, C1-C4 alkyl substituted phenyl, 、N-C1-C 16 Alkyl, C1-C 16 At least one of the alkyl groups; R5 and R6 are each independently selected from Cl, C1-C 16 Any one of alkyl, phenyl, and C1-C4 alkyl-substituted phenyl; R7 is selected from , , Any one of .

5. The preparation method according to claim 4, characterized in that: The co-catalyst is selected from , , Any one of; The cleaning agent is selected from C1-C 16 Alkyl aluminoxane, C1-C 16 Alkyl aluminum, C1-C4 alkyl substituted aluminum chloride, C1-C4 alkyl substituted phenyl aluminum, C6-C 18 Any of aryl aluminum; The polymerization solvent is selected from at least one of toluene, xylene, chlorobenzene, n-hexane, n-heptane and methylcyclohexane.

6. The preparation method according to claim 4, characterized in that: The polymerization reaction temperature is 0-180°C, the propylene pressure is 1-10 atm, and the time is 0.1h-12h; The CH2=CH-(CH2) n -CH3 monomer and CH2=CH-(CH2) m The concentration of the -X polar monomers is independently 0.01-10 mol / L.

7. The preparation method according to claim 4, characterized in that: The cleaning agent and the CH2=CH-(CH2) m -The molar ratio of the polar monomer X is 1.05-1.2:1; The dosage of the main catalyst is 1.0-200 μmol; The molar ratio of the co-catalyst to the main catalyst is (1-20):1, CH2=CH-(CH2) n -The molar ratio of CH3 monomer to main catalyst is (2000-100000):1, CH2=CH-(CH2) m -The molar ratio of the polar monomer to the main catalyst is (2000-50000): 1, the co-catalyst and CH2=CH-(CH2) m The molar ratio of -X polar monomer is (1.05-3):

1.

8. Use of the propylene-based polar polyolefin elastomer as claimed in any one of claims 1 to 3 as a compatibilizer.

9. The use according to claim 8, characterized in that: The compatibilizer is used to compatibilize talcum powder or pine powder; The method of using a compatibilizer to increase the compatibilization of talcum powder or pine powder comprises: Propylene-based polar polyolefin elastomer, polypropylene and a compatibilizing object are blended and extruded to obtain a blended material, wherein the compatibilizing object is talcum powder or pine wood powder; Wherein, in parts by weight, the propylene-based polar polyolefin elastomer is 2-20 parts, the polypropylene is 40-72 parts, and the compatibilizing object is 20-40 parts, which is 100 parts in total.

10. The use according to claim 9, characterized in that: The method for compatibilizing talcum powder or pine powder with a compatibilizer further comprises: Adding an antioxidant to blend with the propylene-based polar polyolefin elastomer, polypropylene and a compatibilizing object; Wherein, the antioxidant is 0.2-0.4 parts by weight.